2015
DOI: 10.5194/acp-15-10529-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the climate and air quality impacts of short-lived pollutants

Abstract: Abstract. This paper presents a summary of the work done within the European Union's Seventh Framework Programme project ECLIPSE (Evaluating the Climate and Air Quality Impacts of Short-Lived Pollutants). ECLIPSE had a unique systematic concept for designing a realistic and effective mitigation scenario for short-lived climate pollutants (SLCPs; methane, aerosols and ozone, and their precursor species) and quantifying its climate and air quality impacts, and this paper presents the results in the context of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
356
6
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 399 publications
(376 citation statements)
references
References 130 publications
13
356
6
1
Order By: Relevance
“…Studies that have used FLEXPART CO concentration fields (χ CO ) have found satisfactory agreement between model output and measurements (Stohl, 2006;Paris et al, 2009;Hirdman et al, 2010;Sodemann et al, 2011;Stohl et al, 2013Stohl et al, , 2015Eckhardt et al, 2015). In the Alaskan Arctic for the day of 18 April 2008, Warneke et al (2009) described a slope of 0.9 for a linear fit between FLEXPART model output of χ CO and airborne measurements of CO with a least-squares correlation coefficient of 0.63.…”
Section: Anthropogenic Pollution Tracer Fieldsmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies that have used FLEXPART CO concentration fields (χ CO ) have found satisfactory agreement between model output and measurements (Stohl, 2006;Paris et al, 2009;Hirdman et al, 2010;Sodemann et al, 2011;Stohl et al, 2013Stohl et al, , 2015Eckhardt et al, 2015). In the Alaskan Arctic for the day of 18 April 2008, Warneke et al (2009) described a slope of 0.9 for a linear fit between FLEXPART model output of χ CO and airborne measurements of CO with a least-squares correlation coefficient of 0.63.…”
Section: Anthropogenic Pollution Tracer Fieldsmentioning
confidence: 98%
“…The CO tracer used for this study is considered as passive in the atmosphere but is removed from the simulation 31 days after emission, thus focusing the simulation on "fresh" pollution. For the CO emissions, ECLIPSE (Evaluating the CLimate and Air Quality ImPacts of Short livEd pollutants) version 4.0 emission data (Klimont et al, 2016;Stohl et al, 2015) are used. For the anthropogenic emissions considered here, the ECLIPSE emissions are based on the GAINS (Greenhouse gas-Air pollution Interaction and Synergies) model (Amann et al, 2011).…”
Section: Anthropogenic Pollution Tracer Fieldsmentioning
confidence: 99%
“…unpaved roads. The ECLIPSE emission datasets have been used in several regional and global atmospheric transport and climate model simulations (AMAP, 2015;Eckhardt et al, 2015;Gadhavi et al, 2015;Lund et al, 2014;Quennehen et al, 2016;Stohl et al, 2013Stohl et al, , 2015Wobus et al, 2016;Yttri et al, 2014) where various aspects of several particulate matter species were addressed. The emissions developed during ECLIPSE also served as the basis for a recently published global particulate number estimate (Paasonen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the emissions described in section 2.2.2, other open burning emissions were derived from the global GFED-4s database (Akagi et al 2011;Andreae et al 2001;Giglio et al 2013;Randerson et al 2012;van der Werf et al 2010) addition to the species in this inventory, ammonia or NH3 emissions, important for calculating secondary particulate matter, were taken from the MIX emission inventory (Li et al 2017; http://meicmodel.org/dataset-mix.html). The model solves for the temporal and spatial evolution of aerosols and gaseous compounds using meteorological data sets, emission inventories, and equations that represent the physics and chemistry of the atmosphere.…”
mentioning
confidence: 99%